Multi-modal mechanophores based on cinnamate dimers - Huan Zhang (Nature Portfolio, 2017)
Mechanochemistry offers exciting opportunities for molecular engineering of stress-responsive properties of polymers. Here the authors show that macrocyclic cinnamate dimers in a polymer chain can undergo dissociation on the sub-second timescale under 1–2 nN stretching to yield a chromophore that then can be optically healed.